Biomass-derived carbons physically activated in one or two steps for CH4/CO2 separation. (May 2022) - Greco, Gianluca; Canevesi, Rafael L.S.; Di Stasi, Christian; Celzard, Alain; Fierro, Vanessa; Manyà, Joan J.
Abstract: The present study aims at evaluating the suitability of producing activated carbons (ACs) derived from wheat straw by a one-step synthesis approach, as an alternative to more conventional two steps production processes (i.e., pyrolysis and subsequent activation). The performance of the produced ACs, in one or two steps, as sustainable and selective CO2 adsorbents for CH4 /CO2 separation is compared. In addition, the influence of pyrolysis conditions on the properties of the resulting two-step ACs is carefully analyzed. We show that the biochar-based precursors of ACs presenting the best textural properties were obtained under mild conditions of maximum temperature and absolute pressure during pyrolysis. The one-step ACs were fully comparable —in terms of textural properties as well as CO2 uptake and selectivity— to those produced by the more conventional two-step synthesis process. In addition, results obtained from breakthrough curve simulations highlight that the best AC in terms of CH4 recovery under dynamic conditions was produced by a one-step activation. Therefore, the one-step process appears to be as an attractive route for the production of engineered carbon materials, which can lead to significant cost savings in large-scale production systems. Graphical abstract: Image 1